ANALISIS TINGKAT KESEHATAN KOPERASI JASA KEUANGAN SYARIAH (STUDI KASUS KJKS BMT BERINGHARJO YOGYAKARTA) - Itsnaini Chusnul Khotimah (Program Studi Perbankan Syariah, 2019)
Since the establishment of the PINBUK Foundation (Small Business Business Incubation Center) which also established the Sharia Cooperative Parent (INKOMSYAH) many BMTs have joined in fostering foundations and helping the community to establish cooperatives throughout Indonesia. KJKS health level analysis is carried out to assess whether a KJKS has an operational level financially or financially or just the opposite. The purpose of this study was to determine the level of health of the Beringharjo Yogykarta BMT KJKS for the period 2013-2014 using descriptive qualitative research methods and assessments that refer to the State Minister for Cooperatives and Small and Medium Enterprises Republic of Indonesia Number: 35.3Per / M.KUKM / X / 2007 concerning guidelines for evaluating the health of Islamic financial services cooperatives and cooperative Islamic financial services units. By using a sample in the form of KJKS BMT Beringharjo Yogyakarta financial statements for the period 2013-2014 researchers calculated the soundness of the bank, documents and observations to strengthen the results of the study. The results of the research conducted can be concluded that in the period 2013-2014 KJKS BMT Beringharjo Yogyakarta experienced an unhealthy condition.